The Need of English for Specific Purposes in Vocational High School - Wen Wahyudi; Jufrizal Jufrizal (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research focuses on the Need Analysis components in English for Specific Purposes (ESP), which are Target Situation Analysis (TSA), Learning Situation Analysis (LSA), and Present Situation Analysis (PSA) based on students and an English teacher at first-grade Electronic Industrial Engineering in learning English for Specific Purpose. The research was conducted using mixed-method as the design. The participants are twelve first-grade students and their English teacher at Electronical Industrial Engineering. The instruments are questionnaires and interviews for both students and the teacher. The result of this research shows in the dimension course preferences 83% wanted to learn English following the material they need in engineering. Then 92% of them need to have good negotiation and instruction understanding proficiency for future occupation. Then, they are weak in speaking, with mastery categorized as low. This result is also supported by their teacher, She has a problem in preparing the appropriate materials because she only followed the previous pattern. Moreover, the students are weak in speaking and reading aspects, thus, they need to improve their skills for their future needs. The conclusion is that the school is required to fulfill students’ needs for improving their skills in ESP.